2019
DOI: 10.21037/qims.2018.10.06
|View full text |Cite
|
Sign up to set email alerts
|

Improved repeatability of subsolid nodule measurement in low-dose lung screening with monoenergetic images: a phantom study

Abstract: Background: To investigate whether monoenergetic images captured with dual-layer spectral computed tomography (CT) can improve the repeatability of subsolid nodule measurement, and whether this approach can further reduce the radiation dose of CT while maintaining its measurement repeatability. Methods: An anthropomorphic phantom with simulated subsolid nodules at three different levels was repeatedly scanned with both conventional single-energy CT and dual-layer spectral CT. A proxy for the measurement repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The latest dual-layer spectral detector CT (SDCT) acquires homologous, in-phase, and temporally synchronized photons from a single source, thereby enabling energysensitive projection data to be obtained simultaneously. The system applies anti-correlated noise suppression and an iterative algorithm, thus reducing image noise and improving image quality (10)(11)(12). Another advantage that SDCT has over other types of dual-energy CT is that it can generate all spectral datasets without the need to pre-set dual-energy protocols, thereby efficient clinical workflow (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…The latest dual-layer spectral detector CT (SDCT) acquires homologous, in-phase, and temporally synchronized photons from a single source, thereby enabling energysensitive projection data to be obtained simultaneously. The system applies anti-correlated noise suppression and an iterative algorithm, thus reducing image noise and improving image quality (10)(11)(12). Another advantage that SDCT has over other types of dual-energy CT is that it can generate all spectral datasets without the need to pre-set dual-energy protocols, thereby efficient clinical workflow (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Mono-energetic reconstructions at 70 keV using dual-energy spectral CT are considered equivalent to conventional CT images acquired using 120 kVp, and several authors found no significant difference in volumetry accuracy between them [ 86 88 ]. In addition, mono-energetic reconstructions improved the repeatability of volumetry at the same radiation dose [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…The measurement repeatability of VMIs for pulmonary nodules were equivalent to that of conventional images using the IR algorithm at a standard dose, suggesting the use of monoenergetic images might allow lung cancer screening at a lower radiation dose. 31 Other data revealed that images at a low single-energy level have lower noise and higher image contrast. 32 Regarding spectral CT, low VMIs exhibited better image quality than conventional images from the same system.…”
Section: Discussionmentioning
confidence: 99%